2005
DOI: 10.1097/01.wnf.0000174933.89758.c9
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine in the Treatment of Focal Tardive Dystonia Induced by Other Atypical Antipsychotics

Abstract: The authors report 2 patients with schizophrenia who developed focal tardive dystonia secondary to treatment with atypical antipsychotics (risperidone, olanzapine). When quetiapine was gradually introduced and other antipsychotics were discontinued, these patients experienced remarkable and sustained improvement of their dystonic symptoms, without loss of psychotic symptom control. The mechanism by which quetiapine may improve tardive dystonia caused by other atypical antipsychotics is unclear. Due to its rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 20 publications
(18 reference statements)
0
10
0
1
Order By: Relevance
“…20,22,[34][35][36][37][38][39] All patients suffering from TD showed remarkable reduction after the replacement of the responsible antipsychotic(s) with quetiapine along with psychosis control. Most patients achieved reduction or elimination of TD with monotherapy, whereas one patient needed to continue taking the initial drug too, for the control of psychosis, in accordance with the observation that amelioration of TD is possible with the addition of quetiapine along with the initial drug at reduced dosage.…”
Section: Discussionmentioning
confidence: 99%
“…20,22,[34][35][36][37][38][39] All patients suffering from TD showed remarkable reduction after the replacement of the responsible antipsychotic(s) with quetiapine along with psychosis control. Most patients achieved reduction or elimination of TD with monotherapy, whereas one patient needed to continue taking the initial drug too, for the control of psychosis, in accordance with the observation that amelioration of TD is possible with the addition of quetiapine along with the initial drug at reduced dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Quetiapine-related TD was noted and described in an early case report about 15 years ago 5). However, some reports also mention contrary findings of quetiapine's ability to relieve TD 1,2,8,9,10,11,12,13). Emsley et al14) found that quetiapine could effectively reduce TD severity in patients with established TD, but the mechanism of this action is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Emsley et al14) found that quetiapine could effectively reduce TD severity in patients with established TD, but the mechanism of this action is unclear. Quetiapine is the atypical antipsychotic most similar to clozapine (without its hematologic side effects) based on receptor and pharmacologic profile, which may explain its treatment effects for TD 11). Quetiapine is believed to express lower affinity for D2 receptors in striatal and extrastriatal regions of brain,15) which could explain the mechanisms by which it can treat or relieve TD side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of case studies, quetiapine was reported to reduce the severity of TD symptoms [142][143][144], while in others it induced TD [145][146][147]. Larger controlled studies are necessary to reach a definite conclusion.…”
Section: Td In Patient Receiving Classical Agentmentioning
confidence: 98%